Microbiota transplant therapy in inflammatory bowel disease: advances and mechanistic insights - Daphne Moutsoglou; Pavithra Ramakrishnan; Byron P. Vaughn (Gut Microbes)
Microbiota transplant therapy is an emerging therapy for inflammatory bowel disease, but factors influencing its efficacy and mechanism remain poorly understood. In this narrative review, we outline key elements affecting therapeutic outcomes, including donor factors (such as age and patient relationship), recipient factors, control selection, and elements impacting engraftment and its correlation with clinical response. We also examine potential mechanisms through inflammatory bowel disease trials, focusing on the interplay between the microbiota, host, and immune system. Finally, we briefly explore potential future directions for microbiota transplant therapy and promising emerging treatments.